A Craniopharyngioma Associated With Elevated Cerebrospinal Fluid HCG Concentrations Misdiagnosed as a Germinoma - Gu, Weijun; Gu, Weizhong; Gu, Yulin; Li, Jie; Yang, Guoqing; Guo, Qinghua; Zang, Li; Du, Jin; Pei, Yu; Ba, Jianming; Lv, Zhaohui; Dou, Jingtao; et al. (Frontiers in Neurology, 2018)
Craniopharyngiomas and germinomas are both rare cranial tumors that most commonly present during childhood or adolescence. Although these tumors have different origins, their clinical and radiological features may be similar. In this article, we report the case of a 35-year female patient with clinical and radiological findings and increased human chorionic gonadotrophin (HCG) levels in the cerebrospinal fluid (CSF) that were consistent with a germinoma; however, the pathological analysis revealed a craniopharyngioma. This case report highlights that HCG, which is regarded as a specific tumor marker for germinomas in the differential diagnosis of intracranial lesions, is also detectable in other kinds of suprasellar tumors, such as craniopharyngiomas.